China's ongoing agricultural reform - Carter, Colin A.; Zhong, Fu-Ning; Cai, Fang (1990 Institute, 1996)
The authors conclude with suggestions for fundamental changes in China's agricultural policy that are needed if the nation is to feed its 1.2 billion people
Keywords: Agrarische hervormingen; Agriculture - Aspect économique - Chine; Politique agricole - Chine; Landwirtschaft; Wirtschaftspolitik; Agriculture and state -- China; Agriculture -- Economic aspects -- China; Agrarreform; Chine - Politique économique - 1976-...; China -- Economic policy -- 1976-2000; China